A Short History of the Formation of Hungarian Legal Terminology - József Szabadfalvi (Rechtsgeschichte - Legal History)
After the founding of the sovereign Hungarian feudal state, Latin became the ›official‹ language of state affairs, legislation, and legal literacy for centuries. Hungarian terminology appeared relatively late, in spite of the fact that basic legal concepts had long been used in the language, especially in the spoken language of oral litigation and disputes. The creation of Hungarian terminology gained new impetus under the inﬂuence of the ideas of the Enlightenment. This process coincided with the so-called language reform and the ›codiﬁcation‹ of the Hungarian literary and common language. An important development for the completion of the Hungarian legal language was the publication of Hungarian translations of legal works and books previously published in Latin from the beginning of the 17th century onwards. Starting at the end of the 18th century, the extension of the official use of the Hungarian language had become the subject of a political struggle between the Viennese court and the Hungarian Estates – one that had a direct effect on the development of the legal language. The uniﬁcation of Hungarian terminology was facilitated by the publication of more than 30 legal vocabularies, an official dictionary, and a glossary in the ﬁrst half of the 19th century. A uniﬁed legal language and adequate terminology, both linguistically and conceptually, had been established in Hungary by the beginning of the 20th century.